2012
DOI: 10.1101/gr.138651.112
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive molecular cytogenetic analysis of chromosome rearrangements in gibbons

Abstract: Chromosome rearrangements in small apes are up to 20 times more frequent than in most mammals. Because of their complexity, the full extent of chromosome evolution in these hominoids is not yet fully documented. However, previous work with array painting, BAC-FISH, and selective sequencing in two of the four karyomorphs has shown that highresolution methods can precisely define chromosome breakpoints and map the complex flow of evolutionary chromosome rearrangements. Here we use these tools to precisely define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 32 publications
(45 reference statements)
2
30
0
Order By: Relevance
“…Additionally, ∼ 98.9% of the breakpoints are localized in CNVs, while only 50% of them are colocalized with SDs. This finding is in concordance with Carbone et al [2006] who analyzed 100 ECBs in gibbons with a resolution of 200 kb and found that 46% of these breakpoints correspond to SDs with respect to the [Carbone et al, 2009;Capozzi et al, 2012]. Recent molecular data by Wilson et al [2015] further underline the correlation and colocalization of CNVs, common fragile sites (CFSs), as well as ECBs.…”
Section: Evolutionary Conserved Breakpoints and Copy Number Variant Rsupporting
confidence: 73%
See 2 more Smart Citations
“…Additionally, ∼ 98.9% of the breakpoints are localized in CNVs, while only 50% of them are colocalized with SDs. This finding is in concordance with Carbone et al [2006] who analyzed 100 ECBs in gibbons with a resolution of 200 kb and found that 46% of these breakpoints correspond to SDs with respect to the [Carbone et al, 2009;Capozzi et al, 2012]. Recent molecular data by Wilson et al [2015] further underline the correlation and colocalization of CNVs, common fragile sites (CFSs), as well as ECBs.…”
Section: Evolutionary Conserved Breakpoints and Copy Number Variant Rsupporting
confidence: 73%
“…Even in the age of next-generation-sequencing, balanced and complex rearrangements as well as repetitive heterochromatic regions and CNVs cannot unambiguously be resolved by an exclusive use of these modern approaches. Therefore, comparative chromosome painting of HSA and HLA provides a necessary overview on the extensive diversity within this group, such as chromosome numbers, composition of syntenic blocks, and type of translocations [Capozzi et al, 2012]. CNVs and fast mapping of euchromatic breakpoints is accomplished by the here applied approach of array painting.…”
Section: Novel Submicroscopic Chromosomal Changes and Previously Undementioning
confidence: 99%
See 1 more Smart Citation
“…One of the interesting primates in terms of VNTR polymorphisms is gibbon, a small ape found in South and Southeast Asia (Matsudaira and Ishida 2010;Meyer et al 2012). Evolution of gibbon was rapid, and it diverged from humans approximately 17-23 million years ago (Capozzi et al 2012). The rate of chromosomal arrangements in gibbons is 10-20 times faster than the standard mammalian rate (Misceo et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…If we assume an all-metacentric karyotype with 32 chromosomes also for the ancestor of the trifoliatus group, the only mode of rearrangement which could change arm combinations in a single step is WART. It is a remarkable parallelism that in the Hylobatidae, one of the mammalian taxa with the highest rate of chromosomal rearrangements [Capozzi et al, 2012], the karyotypes of 2 sibling species, i.e. H. agilis from Sumatra and H. albibarbis from Borneo (a former subspecies of H. agilis ), also differ by a WART [Hirai et al, 2005].…”
Section: Wartmentioning
confidence: 99%